2021
DOI: 10.1177/13623613211009349
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal psychometric evaluation of the developmental disorder parenting stressor index with Japanese parents of children with autism

Abstract: Assessing parenting stress in parents of children with autism has crucial clinical implications because increased parental stress is associated with psychological disorders and personal distress, which can result in worse child–parent relationships. We examined the psychometric properties of a new index for assessing parenting stressors—the Developmental Disorder Parenting Stressor Index and the temporal variability of parenting stressors using longitudinal data of 212 Japanese parents of children with autism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Parenting stress refers to negative psychological experiences, such as anxiety, depression, and self-reproach, associated with the fulfillment of parents’ roles ( Abidin, 1995 ; McStay et al, 2014 ). Several studies have reported that parents of children with ASD suffer from more stress than parents of children without disabilities ( Hutchison et al, 2016 ; Yamane, 2021 ). Furthermore, the stress of raising a child with ASD may be fundamentally different from that experienced by parents of children without disabilities ( Lu et al, 2018 ; Stephenson et al, 2022 ).…”
Section: Instructionmentioning
confidence: 99%
“…Parenting stress refers to negative psychological experiences, such as anxiety, depression, and self-reproach, associated with the fulfillment of parents’ roles ( Abidin, 1995 ; McStay et al, 2014 ). Several studies have reported that parents of children with ASD suffer from more stress than parents of children without disabilities ( Hutchison et al, 2016 ; Yamane, 2021 ). Furthermore, the stress of raising a child with ASD may be fundamentally different from that experienced by parents of children without disabilities ( Lu et al, 2018 ; Stephenson et al, 2022 ).…”
Section: Instructionmentioning
confidence: 99%